Association of rs440446 in the APOE intron region with multidimensional cognitive function, lipid/metabolic markers, and spontaneous neural activity in Chinese urban community-dwelling older adults - Wang, Zhiyuan; Guo, Hongyu; Li, Jianshuai; Hu, Xuejie; Li, Xin; Sun, Jinping (Frontiers in Neuroscience, 2025)
Backgroundrs440446 (+ 113G/C), located in the intron of the APOE gene, has unclear effects on cognition, blood lipids, metabolic markers, and neural activity in older Chinese adults.MethodsA total of 505 older adults from communities in Qingdao were enrolled and categorized into C-allele carriers (n = 451) and GG homozygotes (n = 54) based on the sequencing result. Neuropsychological tests, lipid/metabolic markers (n = 326), and resting-state fMRI (rs-fMRI) data (n = 216) were collected. Multivariable linear regression was used to assess associations between rs440446 and cognitive performance, lipids, and metabolic indicators. Subgroup analyses stratified by age, gender, and APOE ε4 status were conducted, along with interaction tests. Propensity score matching (PSM) was applied to balance sample sizes in the rs-fMRI subgroup. Fractional amplitude of low-frequency fluctuations (fALFF) was used to evaluate differences in spontaneous neural activity, and Pearson correlations were calculated between fALFF values and cognitive function.Resultsrs440446 GG homozygotes were associated with poorer language function. This association was consistently observed in female, ≥ 60 years old, and APOE ε4 non-carrier subgroups. However, no significant relationship was found between the GG genotype and lipid or metabolic markers. In fALFF analysis, GG homozygotes exhibited decreased spontaneous neural activity in the left middle occipital gyrus (MOG.L) and right cuneus (CUN.R), while showing increased activity in the right superior temporal gyrus (STG.R) and left fusiform gyrus (FFG.L). Additionally, fALFF values in the CUN.R were positively correlated with attention, whereas fALFF values in the STG.R were negatively correlated with memory.Conclusionrs440446 GG homozygote may be associated with alterations in language function and spontaneous neural activity among older adults.